Quá comando mi: coronelismo na região colonial italiana: práticas de cooptação e coerção cel. Agilberto Attílio Maia no município de Guaporé (1912-1930) - Balbinot, Giovani (2018)
This Doctoral Thesis intends to analyze, through the performance of Cel. Agilberto Attílio Maia in the municipality of Guaporé, as practices of cooptation, coercion and formation of the support network of the coronelist operating in the region of Italian colonization during the first week of the twentieth century. Analyzing a trajectory of the individual in especial, strange to the region, which was eternalized before a direction in the municipal intentionality between 1912 and 1937, we also wish to delineate the profile of the colonel in the Italian colonization region, perceiving its peculiarities and similarities, a colonial reality, with the coronelismo manifested in the other regions of Rio Grande do Sul and without the return of Brazil. What same time, they seek to encompass the digitizing of immigrants and their descendants in the dynamics of the "maneuver", but rather as the conscious and active, even if, at this time, with political horizon of ascent. The evaluation of colonial students are in the participation of coamaration of colonists are in the understanding of cooptation of colonists in the cooptation of hierarchy PRR municipal. On the other hand, in the context of coercion, with the appointment of prosecutors, district, county and Superior Court judges, it issues a right to lodge its rights in favor of the components of its network of commitments and to the detriment of its opponents, with a organization of a police structure that includes Military Brigade, National Guard, administrative and judicial police, and, finally, armed bodies, whether official or not, that participate in electoral fraud, purchases of votes, intimidation and violence against the recalcitrant of the network of contracts by colonel. Thus, they understand the existence of the coronelist phenomenon, however, adapted as conditions and cultural, economic, social and political specificities of the region of Italian colonization.